Economic Traits and Production Performance of Nandanam Quail Reared at Different Cage Stocking Densities - Pandian, C; Sudersan, A; Valvan, S Ezhil; Omprakash, AV (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
This study was carried out to assess the effect of different cage stocking densities on the production performance of Nandanam quail III reared up to 42 days. Three hundred day old Nandanam quail III were randomly assigned to 2.5 x 1.5 ft cages and distributed with 3 treatments (20, 25 and 30 quails per cage or 0.17, 0.14 and 0.11 sq. ft per quail, respectively) and 4 replicates. There were significant differences among treatments for bi-weekly body weight, feed consumption, feed conversion ratio and net profit per bird. There was a reduction (P
Keywords: Cage stocking density; Nandanam quail III; Production performance